Psicologia escolar e políticas públicas: significações sobre inserção e atuação profissional - Nakamura, Felipe Kazuo da Mata (2023)
This research lies at the intersection of School Psychology and public policies, with the aim of analyzing the possibilities and challenges found in public policies for the inclusion and performance of school psychologists in public basic education in the state of Goiás. In recent decades, driven by the critical movement, public policies have become a central field for reflection, action, and study within School Psychology. In the educational context, public policies are essential, as they directly influence the management and functioning of education, impacting the inclusion and performance of school psychologists. The debate on public policies is framed within capitalist society, considering their development as actions of the State that reflect social class interests and prioritize social issues. In capitalist society, public policies reflect the tension between the interests of capital accumulation and the needs of the population. Guided by historical-dialectical materialism and based on Historical-Cultural Psychology, this research seeks to understand material reality through the meanings and interpretations that circulate within public policies. To achieve this, mapping and analysis of laws addressing the intersection between psychology and education at the municipal, state, and federal levels were conducted, along with interviews with psychologists to understand how the proposals for inclusion and performance in public policies are perceived. The results of the documentary mapping identified 32 laws across the three spheres, analyzed under two thematic axes: the inclusion of psychologists in education and the professional perspectives of their practice. The legislative overview reveals opportunities for inclusion, but also highlights divergent perspectives on professional practice, which generate challenges. Interviews with psychologists helped to understand their role in the development and implementation of public policies, as well as the conceptions embedded in the laws regarding School Psychology. The research acknowledges the opportunities and potential of public policies for the inclusion of psychologists in basic education, but also recognizes the challenges arising from the contrasting expectations and forms of professional practice expressed in these policies. Furthermore, it emphasizes the need for the active participation of psychologists in the policy-making process. The knowledge generated contributes to strengthening the understanding of School Psychology in Goiás, the inclusion of psychologists in the state’s public education system, the expansion of educational actions, and the recognition of the importance of psychologists in the advancement of educational public policies.